Contributions to the Theory of Nonlinear Oscillations, Volume II (Annals of mathematics studies., 1952)
These two new collections, numbers 28 and 29 respectively in the Annals of Mathematics Studies, continue the high standard set by the earlier Annals Studies 20 and 24 by bringing together important contributions to the theories of games and of nonlinear differential equations.